2007
DOI: 10.1262/jrd.18049
|View full text |Cite
|
Sign up to set email alerts
|

Arginase Alteration in the Reproductive System of Alloxan-Diabetic Dogs

Abstract: Abstract. This study was conducted to evaluate possible alteration in the activity of arginase, an important enzyme of cell proliferation and vascular smooth muscle contraction regulator in diabetics, that may be correlated with low fertility in diabetic patients. In this investigation, 6 apparently healthy adult male dogs were selected and divided in two groups, diabetics and non-diabetics. Diabetes mellitus was induced in one group by intravenous (IV) injection of alloxan (100 mg/kg). Dogs with a fasting blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Although, the serum testosterone level declined significantly at the end of 36 days in STZ treated group, subsequent estimation on 72 day did not show any difference between control and diabetic groups. The review of earlier studies on the effect of hyperglycemia on plasma testosterone level has demonstrated conflicting results [16][17][18][19] possibly due to differences in study models and diabetes induction methods. With the decline in testosterone level at 36 days interval, we speculated an aberrant spermatogenesis in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the serum testosterone level declined significantly at the end of 36 days in STZ treated group, subsequent estimation on 72 day did not show any difference between control and diabetic groups. The review of earlier studies on the effect of hyperglycemia on plasma testosterone level has demonstrated conflicting results [16][17][18][19] possibly due to differences in study models and diabetes induction methods. With the decline in testosterone level at 36 days interval, we speculated an aberrant spermatogenesis in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Two parallel mechanisms were proposed to cause diabetes-related alterations in Leydig cells: (1) the effect of hypoinsulinemia on serum LH levels and (2) the combined effects of the decreased levels of LH and insulin on Leydig cells [25]. Moreover, diabetes mellitus was reported to alter the activity of arginase (an enzyme important in cell proliferation) in the reproductive system, which may impair Leydig cell proliferation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes was confirmed at one week after the alloxan injection by the presence of fasting blood glucose level of above 11.10 mmol/L (Jelodar et al, 2007). Polyuria and polydipsia, the clinical signs of diabetes, were also noted.…”
Section: Induction Of Diabetesmentioning
confidence: 96%
“…Diabetes mellitus was induced in dogs used for the study by intravenous (IV) injection of alloxan monohydrate (Sigma, USA) at a dose of 100 mg/kg (Jelodar et al, 2007;Kim et al, 2006). The dogs were fasted for 24 hours prior to the diabetes induction (Kim et al, 2006).…”
Section: Induction Of Diabetesmentioning
confidence: 99%